2012
DOI: 10.1128/mbio.00252-12
|View full text |Cite
|
Sign up to set email alerts
|

Streamlining and Core Genome Conservation among Highly Divergent Members of the SAR11 Clade

Abstract: SAR11 is an ancient and diverse clade of heterotrophic bacteria that are abundant throughout the world’s oceans, where they play a major role in the ocean carbon cycle. Correlations between the phylogenetic branching order and spatiotemporal patterns in cell distributions from planktonic ocean environments indicate that SAR11 has evolved into perhaps a dozen or more specialized ecotypes that span evolutionary distances equivalent to a bacterial order. We isolated and sequenced genomes from diverse SAR11 cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
340
4
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 272 publications
(387 citation statements)
references
References 94 publications
31
340
4
2
Order By: Relevance
“…Many of the genomic streamlining features observed in Cand. IA genome, such as small genome size, small intergenic regions, low incidences of gene duplication and low number of rRNA operons, have been associated with specific trophic lifestyles, mainly oligotrophy and obligate symbiosis (Giovannoni et al, 2005;Lauro et al, 2009;Walker et al, 2010;Grote et al, 2012;Swan et al, 2013), where they appear to be a reflection of the accessibility of nutrients, as well as the occurrence of genetic drift in obligate symbionts (Mira et al, 2001;Wernegreen, 2002;Giovannoni et al, 2005;Oakeson et al, 2014). However, detailed comparative analysis of the metabolism and genomic features of Cand.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the genomic streamlining features observed in Cand. IA genome, such as small genome size, small intergenic regions, low incidences of gene duplication and low number of rRNA operons, have been associated with specific trophic lifestyles, mainly oligotrophy and obligate symbiosis (Giovannoni et al, 2005;Lauro et al, 2009;Walker et al, 2010;Grote et al, 2012;Swan et al, 2013), where they appear to be a reflection of the accessibility of nutrients, as well as the occurrence of genetic drift in obligate symbionts (Mira et al, 2001;Wernegreen, 2002;Giovannoni et al, 2005;Oakeson et al, 2014). However, detailed comparative analysis of the metabolism and genomic features of Cand.…”
Section: Discussionmentioning
confidence: 99%
“…As would be expected from a low percentage of unique genes in the SAGs, much of the metabolism of these organisms appeared to be similar to that of the surface strains, particularly the subclade Ia organisms. Collectively, the Ic subclades were predicted to be obligate aerobic organisms, with cytochrome c oxidase as the sole predicted terminal reductatse, a complete tricarboxylic acid cycle, conserved lesions in several glycolytic pathways (Schwalbach et al, 2010), a reliance on reduced sulfur compounds (Tripp et al, 2008) and pathways for the metabolism and oxidation of small organic molecules such as amino/carboxylic acids and one-carbon and methylated compounds (Yilmaz et al, 2011;Grote et al, 2012;Carini et al, 2012;Supplementary Table S1).…”
Section: Subclade Ic Relative Abundance In Metagenomic Datasetsmentioning
confidence: 99%
“…Although the majority of research has focused on the SAR11 clade in the euphotic and upper mesopelagic zones, multiple studies have demonstrated evidence of substantial SAR11 populations deeper in the mesopelagic, as well as in the bathy-and even hadopelagic (46000 m) realms (Martin-Cuadrado et al, 2007;Konstantinidis et al, 2009;Schattenhofer et al, 2009;Quaiser et al, 2010;Swan et al, 2011;Eloe et al, 2011a, b;King et al, 2013). SAR11, or the 'Pelagibacterales,' is a diverse group, spanning at least 18% 16S rRNA gene divergence, and is comprised of subclades with unique spatiotemporal distributions (ecotypes) that follow seasonal patterns (Field et al, 1997;Carlson et al, 2009;Giovannoni and Vergin, 2012;Grote et al, 2012;Vergin et al, 2013). All genome-sequenced representatives are characterized by small (1.3-1.4 Mbp), streamlined genomes with low GC content, few gene duplications and an obligately aerobic, heterotrophic metabolism generally focused on oxidation of low-molecularweight carbon compounds, such as carboxylic and amino acids, osmolytes and methylated compounds (Schwalbach et al, 2010;Yilmaz et al, 2011;Carini et al, 2012;Grote et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations